Joint Forest Management in Retrospect - Melkani, V. K. (Indian Forester, 2011)
Joint Forest Management (JFM) has added a new dimension to the overall domain offorestry and forest management in India. As an inclusive and participatory process it attempts to build stakes for eliciting local community’s involvement in the protection, regeneration and development of forests. Since the beginning of the initiatives with the generic guidelines from the Central government in 1990, the process of JFM has graduated to significant levels and adopted by all t he States. The results of JFM implementation have so far been mixed. This is because as a process, it evolves as the understanding the concept and its relevance and the implementation capacity ofthe partners enhances. Some critical issues - building vibrant village level instit utions, defined roles and responsibilities of partners, transparent set of regulations for benefit sharing among participating communities, management capacities of stakeholders for joint planning and implementation, improved co-ordination and control mechanisms have a bearing on the successful outcome of JFM. These issues need to be diagnosed, refined and sincerely followed up to enable the field level interventions result in outcomes where the welfare of the local communities is genuinely linked with the wellbeing of the interface forests and the larger vision of JFM to establish people’s institutions to take stewardship of conservation action in partnership of other government and local institutions with enhanced synergies and convergence is achieved and sustained.